2005
DOI: 10.2139/ssrn.774684
|View full text |Cite
|
Sign up to set email alerts
|

Does Watching TV Make Us Happy?

Abstract: Watching TV is a major human activity. Because of its immediate benefits at negligible immediate marginal costs it is for many people tempting to view TV rather than to pursue more engaging activities. As a consequence, individuals with incomplete control over, and foresight into, their own behavior watch more TV than they consider optimal for themselves and their well-being is lower than what could be achieved. We find that heavy TV viewers, and in particular those with significant opportunity cost of time, r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
84
0
2

Year Published

2009
2009
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 83 publications
(92 citation statements)
references
References 75 publications
6
84
0
2
Order By: Relevance
“…Additionally, the measurement level is likely to be the cause of some of the nonsignificant correlations, for instance, with watching TV. Other studies (Bruni & Stanca, 2006, 2008: Delle Fave & Bassi, 2003Frey et al, 2005) found that watching TV negatively influences happiness. As most people watch TV daily, no distinction could be made between heavy users and regular viewers.…”
Section: Why No Effect Of Other Leisure Activities?mentioning
confidence: 94%
“…Additionally, the measurement level is likely to be the cause of some of the nonsignificant correlations, for instance, with watching TV. Other studies (Bruni & Stanca, 2006, 2008: Delle Fave & Bassi, 2003Frey et al, 2005) found that watching TV negatively influences happiness. As most people watch TV daily, no distinction could be made between heavy users and regular viewers.…”
Section: Why No Effect Of Other Leisure Activities?mentioning
confidence: 94%
“…Bruni and Stanca (2006) find suggestive evidence that people who watch TV for more than two hours per day only experience half the increase in life satisfaction from a rise in income compared to low-frequency TV viewers. Finally, Frey et al (2007) analyse data on life satisfaction and TV consumption in Europe and provide evidence that TV viewers are on average less satisfied with their financial situation even after controlling for actual income. Clark and Senik (2010a) is, to our knowledge, the only study which looks beyond TV and assesses the role of the internet technology.…”
Section: Introductionmentioning
confidence: 99%
“…Early sociological studies on computer-mediated communication shared the fear that the Internet would cause a progressive reduction in social interactions, just as the activity of watching TV does (Bruni and Stanca 2006;2008;Frey et al 2007). The main argument shared by Internet skeptics was based on the presumption that the more time people spend using the Internet during leisure time, the more time has to be detracted from social activities (Katz et al 2001;Nie et al 2002, Attewel et al 2003Gershuny 2003;Robinson and Martin 2010).…”
Section: Related Literaturementioning
confidence: 99%